Endotoxicosis indices as means of prognosis in surgical sepsis caused by purulent-necrotic complications of sugar diabetes - Pavliak, A. Ya.; Pyptiuk, O. V. (Modern medical technology, 2019)
Purpose of the study. to study how the consequences of surgical sepsis caused by purulent-necrotic complications of sugar diabetes depend on the dynamics of endotoxicosis indices in the course of treatment. Material and methods. The research included 30 patients with the symptoms correlating with the criteria for surgical sepsis caused by purulentnecrotic complications of sugar diabetes. The patients had their level of endotoxicosis measured and the severity of their condition evaluated according to the scale. Results. 26 patients were discharged from hospital due to their recovery, 4 patients died. The purulent-necrotic complications lead to the development of intoxication syndrome and sepsis causing, in its turn, the decompensating of the disease, poly-organic insufficiency and the high lethality. Despite the conservative and surgical treatment carried out, the high indices of endogenic intoxication in the dynamics of the treatment proved to be a bad prognostic sign. Conclusion. the monitoring of endogenous intoxication in patients with surgical sepsis caused by the purulent-necrotic complications of sugar diabetes in the treatment dynamics proves to be an important diagnostic and prognostic element helping to correct the treatment tactics and diminish the lethality.